SCHEMATICHESKIY ANALYSIS TSIFROVYX IZMERITELNYX PRIBOROV - Tairov Baxtiyor Boboqulovich; Karshiyev Zokhidjon (American Journals, 2023)
In the article, the conversion of the measured value entered into digital measuring instruments into a digital code occurs automatically. Information about digital measuring devices for automatic conversion of the measured value into a digital code is highlighted. Based on this, the article reflects some types of digital measuring devices, and you will get a conclusion about the measurement results of digital computing devices and the quantitative qualities of their products.
Keywords: Analog, compensator, quantization, discrete error, digital voltmeter, electromechanical relay, microprocessor.